Dakwah Berbasis Komunitas Digital: Strategi Shift Pemuda Hijrah dalam Membangun Komunitas Online yang Aktif dan Produktif - Wahidin; Yoga Agus Yulianto; Canra Krisna Jaya (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The rapid development of digital technology has transformed Islamic preaching in Indonesia from a conventional activity into a dynamic and participatory practice within the digital sphere. This study aims to analyze the strategies of Shift Pemuda Hijrah in building and managing an active and productive digital-based da’wah community. Using a qualitative descriptive approach through content analysis of social media and documentation of community activities, this research identifies three key strategies underlying Shift’s success: personal branding, emotional narrative, and multiplatform optimization. Strong personal branding creates an authentic and relatable image of preachers among urban youth. Emotional narratives emphasizing spiritual experiences and affective connections strengthen emotional bonds between preachers and audiences. Meanwhile, multiplatform strategies enable broader outreach to diverse audience segments through adaptive content formats. The findings demonstrate that the combination of these three strategies forms a model of digital community-based da’wah that enhances participation, interaction, and sustainability of Islamic propagation in the digital age. This study contributes theoretically to the development of digital da’wah literacy and offers practical insights for Islamic organizations in managing online communities effectively and sustainably. Keywords: Digital da’wah, online community, personal branding, emotional narrative, multiplatform strategy, Shift Pemuda Hijrah